Age‐related changes in hepatic expression and activity of drug metabolizing enzymes in male wild‐type and breast cancer resistance protein knockout mice. (24th August 2018) - Zheng, Haihui; Wang, Liping; Zeng, Sijing; Chen, Jiamei; Wang, Haojia; Yu, Jia; Gong, Xia; Jiang, Huangyu; Yang, Xia; Qi, Xiaoxiao; Wang, Ying; Lu, Linlin; et al.
Abstract: This study aimed to reveal age‐related changes in the expression and activity of seven hepatic drug metabolizing enzymes (DMEs) in male wild‐type and breast cancer resistance protein knockout (Bcrp1 −/− ) FVB mice. The protein expression of four cytochrome P450 (Cyps) (Cyp3a11, 2d22, 2e1, and 1a2), and three UDP‐glucuronosyltransferases (Ugts) (Ugt1a1, 1a6a, and 1a9) in liver microsomes of wild‐type and Bcrp1 −/− FVB mice at different ages were determined using a validated ultra high performance liquid chromatography with tandem mass spectrometry (UHPLC–MS/MS) method. The activities and mRNA levels of these DMEs were measured using the probe substrates method and real‐time PCR, respectively. In the liver of wild‐type FVB mice, Cyp3a11, 2d22, 2e1, 1a2, Ugt1a1, and 1a6a displayed maximum protein levels at 6–9 weeks of age. Cyp1a2, Ugt1a1, 1a6a, and 1a9 showed maximum activities at 6–9 weeks of age, whereas Cyp3a11, 2d22, and 2e1 showed maximum activities in 1–3‐week‐old mice. Additionally, most of the DMEs showed maximum mRNA levels in 17‐week‐old mice liver. Compared with wild‐type FVB mice, the protein levels of these DMEs showed no significant changes in Bcrp1 −/− FVB mice liver. However, the activity of Cyp2e1 was increased and that of Cyp2d22 was decreased. In conclusion, t he seven hepatic DMEs in FVB mice liver showed significant alterations in an isoform‐specific manner with increased age. Although the protein levels of these DMEs showed no significant changes, the activities of Cyp2e1 and 2d22 were changed in Bcrp1 −/− mice.